Edgar Allan Poe e Mário de Sá-Carneiro: os fantasmas e a criação literária do fantástico - Nestarez, Oscar Andrade Lourenção (2016)
This dissertation proposes a reflection about the fantastic mode in literature in the light of a fundamental operation of the cognitive process: the phantasms produced by the imagination. The investigation occurs through a comparative reading between two narratives Edgar Allan Poe s Ligeia (1838) and Mário de Sá-Carneiro s The Great Shadow (1915) , having by theorical support the studies from Remo Ceserani (The Fantastic, 1996), Irène Bessière (Le récit fantastique la poétique de l incertain, 1974) and Giorgio Agamben (Stanzas: word and phantasm in western culture, 1977), as well as Poe s critical reflections found in The philosophy of composition (1845), The poetic principle (1850) and Marginalia (1849) about the links between imaginary phantasms and poetical creation. Taking into consideration the significative diferences between the two texts either by the temporal distance or by the fantastic characteristics (more notable in Ligeia ) , this project asks how the root of the fantastic mode in literature can relate with the imaginative phantasms produced in terms of plot and, more specifically, enunciation. The hypothesis is that both Ligeia and The Great Shadow point to the creation of phantasms by the imaginative faculty as the responsable for the effects of the fantastic. This happens though the singularity of a central enunciative process: the spectral apparitions in both plot and in the multiple visions of the narrator in the poetic-phantasmatic discourse, marked by the crisis in representation. The comparative analysis reveals that the phantasm-fantastic relation manifests itself in both texts, although in different terms: in Ligeia , the procedures of the fantastic mode are everywhere spectres, doubles, projections between light and shadow and terror caused by gothic ambience; and, underneath this plan, lies the narrator-author s phantasmatic discourse. In The Great Shadow , on the other hand, excels the sensationist-phantasmatic narration on the form of a diary, leaving the plot and its phantasmagoric ambiance in second plan